Penggunaan Microsoft Excel dalam Memprediksi Aliran Fluida dalam Packed Bed - Hidayati, Hidayati; Supardan, Muhammad Dani (Jurnal Rekayasa Kimia & Lingkungan, 2012)
Flow distribution is often a problem in the operation of the packed bed reactor. The problem is often referred as flow maldistribution and formation of localized hot spot region. This research is generally aimed to predict fluid flow distribution in the packed bed containing porous media by finite difference method using the software MS. Excel. Model verification result shows conformity between analytic method and result of calculation. Simple study of the finite difference method using the software MS. Excel can describe the fluid velocity profile in a packed bed containing porous media. This profile is similar with experiment of Kufner and Hofmann (1990) and Stephenson and Stewart (1986). The simulation was performed to determine the effect of process variables on the fluid flow velocity profile. Particle diameter influences fluid flow velocity. Bulk porosity also influences fluid flow velocity at axis up to certain distance from wall of reactor. Keywords: finite difference method, flow distribution, packed bed reactor